Tanggung Jawab Produsen Rokok terhadap Bahaya Rokok Menurut Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Kosumen dan Undang-Undang Nomor 36 Tahun 2009 tentang Kesehatan - Ryan .; Ermanto Fahamsyah (Fakultas Hukum Universitas Tarumanagara, 2018)
Consumer Protection Law regulates the legal protection of consumers and is intended to regulate the responsibilities and obligations of business actors / producers. However, there are still a number of producers who in carrying out business activities that still violate the provisions in the UUPK, one of which is cigarette producers. Therefore, the author propose a problem about how cigarette manufacturers' responsibility for the dangers of cigarettes according to the Consumer Protection Law and the Health Law. The author examines the problem by using normative legal research methods that use secondary data. From the results of the study concluded that the responsibility of cigarette producers to the dangers of cigarettes according to the Consumer Protection Law and the Health Law is that cigarette producers must be responsible for providing compensation in the form of bearing medical expenses for diseases caused by cigarettes themselves and providing honest, clear and correct information about the product, and change the results of the product to be in accordance with the standard quality of goods and / or services that already exist.